Influence of Rearing System on Sows’ Prolificacy during Gestation - Cornelia Petroman (Scientific Papers Animal Science and Biotechnologies, 2023)
In females reared in individual crates until early control of gestation and in common crates (8-16 heads), prolificacy did not reach values that differ depending on the rearing system: there is a statistically insignificant difference in t-test (p>0.05). In gestating sows reared in individual crates, the difference was significant during the entire gestation period compared to group rearing: 11.51±0.85 compared to only 11.13±0.68 in collective rearing. Though there are better results from the point of view of sows’ prolificacy when reared in individual crates during the entire gestation, this rearing system is not recommendable because of the high financial efforts caused by technology and because separation has negative influences on sows’ behaviour depending on reproduction and health state of gestating females.